2004
DOI: 10.1159/000080471
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic and Fibrinolytic Response to Nasal Desmopressin in Hemodialysis Patients

Abstract: Objective: To evaluate the effect of desmopressin (DDAVP) on hemostatic parameters during dialysis and in the interval between dialysis sessions. Subjects and Methods: Fifteen patients dialyzed twice weekly at least for 1 year and 15 healthy volunteers serving as a control group were enrolled in the study. Bleeding time, platelet count, prothrombin time, activated partial thromboplastin time, tissue plasminogen activator (tPA), plasminogen activator inhibitor (PAI-1), euglobulin clot lysis time, protein C, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…the current study showed that there were statistically significant differences between the mean of APTT in HD patients and those of the control group. This finding agreed with the results obtained by Ulusoy et al, (2004).…”
Section: Discussionsupporting
confidence: 93%
“…the current study showed that there were statistically significant differences between the mean of APTT in HD patients and those of the control group. This finding agreed with the results obtained by Ulusoy et al, (2004).…”
Section: Discussionsupporting
confidence: 93%
“…But the finding in this study is not consistent with Yeniçerioglu et al 16 who reported a significant decrease in circulating platelets post-HD when compared to the pre-HD counts. The decrease in platelets counts post-HD may be due to either the HD procedure itself, through the interaction of blood with membranes that may activate complement (Galbusera et al 14 ) or to the heparin used during dialysis was one of the factors accounting for the increased platelet aggregation after dialysis as previously reported by Charvát et al 17 . In a previous study by Docci et al 18 stated that the dialysis membrane composition is a major factor influencing haemodialysis-associated platelet loss.…”
Section: Resultsmentioning
confidence: 76%
“…DDAVP's reducing effect on bleeding time starts within 1 h and continues for 4-8 h. Bleeding time returns to normal in 24 h (Mannucci et al, 1983;Galbusera et al, 2009). DDAVP has been shown to effectively reduce bleeding time when administered intravenously (0.3 microg⁄kg) by the subcutaneous and intranasal routes (Mannucci et al, 1983;Shapiro & Kelleher, 1984;Ulusoy et al,2004;Viganò et al, 1989). One of the things that must not be forgotten in desmopressin therapy is that efficacy may decline with increasing use, probably in association with a decline in endothelial vWF stores (Canavese et al, 1985).…”
Section: Desmopressinmentioning
confidence: 99%